Doctoral writing and the politics of citation use - Badenhorst, Cecile; Arif, Abu; Quintyne, Kelvin (Discourse and Writing/Rédactologie, 2022)
Conventions shape scholarly writing and citations practices are one set of conventions that dominate how and what we write. Yet, many of these practices naturalize exclusion and discrimination in a way that becomes normalized and, consequently, invisible. For doctoral students, learning the conventions of citing is part of developing an identity around scholarship, research and writing. In this paper, we examine our own experiences of the politics of citations to understand our socialization processes and resistances. We use an autoethnographic narrative approach to frame this qualitative study. Our findings show how citation use abounds with the contradictions and paradoxes in our doctoral writing journeys where the pressure to succeed can compromise identity-building as ethical scholars. Each of us has many needs and multiple positionalities and resisting the naturalizing grammar of citations can be complicated. Yet, once aware of the politics of citations, one cannot go back to being unaware.